New Sincerity and Commitment to Emotion in Dorothea Lasky’s Poetry - Siltanen Elina (United Kingdom, 2022)
“New Sincerity”, a renewed attention to sincerity, has been connected to metamodernism, a periodizing term that marks a tension between irony and sincerity and an extension of modernism and postmodernism. While both New Sincerity and metamodernism have been discussed in relation to fiction and the other arts, they have not been widely considered in poetry. The article considers the associations of the term New Sincerity in US poet Dorothea Lasky’s work, placing her work in the context of metamodernism. With reference to metarepresentation, a cognitive science term that refers to conceptualising what others think, I argue that in Lasky’s poems, New Sincerity functions as a persuasive tonal orientation that exhibits sincerity’s vexed position as both seemingly naïve and necessary. Lasky’s poems make use of the human mind’s metarepresentational capacity as they fluctuate between sincerity and irony.